Cost comparison analysis of open versus laparoscopic distal pancreatectomy. Issue 10 (16th June 2014) - Rutz, Daniel R.; Squires, Malcolm H.; Maithel, Shishir K.; Sarmiento, Juan M.; Etra, Joanna W.; Perez, Sebastian D.; Knechtle, William; Cardona, Kenneth; Russell, Maria C.; Staley, Charles A.; Sweeney, John F.; Kooby, David A.
Abstract Background In comparison with open distal pancreatectomy (ODP), laparoscopic distal pancreatectomy (LDP) is associated with fewer complications and shorter hospital stays, but comparative cost data for the two approaches are limited. Methods Records of all distal pancreatectomies carried out from January 2009 to June 2013 were reviewed and stratified according to operative complexity. Patient factors and outcomes were recorded. Total variable costs (TVCs) were tabulated for each patient, and stratified by category [e.g. 'floor', 'operating room' (OR), 'radiology']. Costs for index admissions and 30‐day readmissions were compared between LDP and ODP groups. Results Of 153 procedures, 115 (70 LDP, 45 ODP) were selected for analysis. The TVC of the index admission was US$3420 less per patient in the LDP group (US$10 480 versus US$13 900; P = 0.06). Although OR costs were significantly greater in the LDP cohort (US$5756 versus US$4900; P = 0.02), the shorter average hospitalization in the LDP group (5.2 days versus 7.7 days; P = 0.01) resulted in a lower overall cost. The total cost of index hospitalization combined with readmission was significantly lower in the LDP cohort (US$11 106 versus US$14 803; P = 0.05). Conclusions In appropriately selected patients, LDP is more cost‐effective than ODP. The increased OR cost associated with LDP is offset by the shorter hospitalization. These data clarify targets for further cost reductions.